Effects of functional training after orthognathic surgery on masticatory function in patients with mandibular prognathism - Nobuhiko Kawai; Manami Shibata; Masahiko Watanabe; Shinya Horiuchi; Kenji Fushima; Eiji Tanaka (Elsevier, 2020)
Background/purpose: Even after surgical orthodontic treatment, the level of masticatory function in patients with jaw deformities is still lower than that of healthy subjects. The purpose of this study was to evaluate the effects of functional training program using gum chewing exercise after orthognathic surgery on masticatory function in patients with mandibular prognathism. Materials and methods: The study subjects were 16 patients with mandibular prognathism who underwent orthognathic surgery and 8 individuals with normal occlusion. Patients were divided into two groups (training group and non-training group; n = 8 per group). Functional training included gum chewing exercise and patient-education about masticatory function. The training; gum chewing exercise of 5 min twice a day for 90 days, started at 3 months after surgery. For each subject, electromyographic activities of masseter and temporalis muscles during maximum voluntary clenching (MVC) and jaw movement during gum chewing were recorded before and after surgical orthodontic treatment. Two parameters; activity index (AI: ratio of activity of masseter and temporalis muscles) and error index (EI: ratio of the number of abnormal chewing patterns), were used. Results: In the training group, the AI value during MVC increased significantly and the EI value during gam chewing decreased significantly after surgical orthodontic treatment (AI: p < 0.01; EI: p < 0.01), indicating the improvement of activity balance of masseter and temporalis muscles and conversion of the jaw movement from abnormal to normal pattern (p < 0.01). Conclusion: Our findings suggested that functional training using the gum chewing and patient-education exercise improved masticatory function in patients with mandibular prognathism.